Endoscopic surgery for intraconal orbital tumors Endoskopische Chirurgie bei intrakonalen Orbitatumoren - Müller, Sarina Katrin; Bleier, Benjamin S. (HNO, 2022)
Traditionally, external craniofacial approaches have been used for orbital tumor resection. Over the last 30 years, endoscopic sinonasal and skull base techniques have become widely used throughout the world. These experiences paved the way for the extension of transnasal endoscopic techniques to the intraconal orbit. Transnasal endoscopic intraconal surgery has several advantages regarding morbidity and outcome as compared with purely external approaches. However, the anatomical knowledge and experience of the surgeon is crucial for the success of the surgery. Endoscopic approaches for intraconal tumor removal are feasible for medial and inferior lesions as well as for lesions lateral to the optic nerve provided they remain inferior to the “plane of resectability” and no optic nerve retraction is required. As intraorbital tumors are rare, new international staging systems including CHEER (Cavernous Hemangioma Exclusively Endonasal Resection) and ORBIT (Orbital Resection by Intranasal Technique) help to standardize safety, efficacy, and outcome.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Craniofacial; Diplopia; Endoscopy; Intraorbital tumors; Transnasal